Effects of achievement differences for internal/external frame of reference model investigations: A test of robustness of findings over diverse student samples. (12th November 2017) - Schmidt, Isabelle; Brunner, Martin; Preckel, Franzis
Abstract : Background: Achievement in math and achievement in verbal school subjects are more strongly correlated than the respective academic self‐concepts. The internal/external frame of reference model (I/E model; Marsh, 1986, Am. Educ. Res. J., 23, 129) explains this finding by social and dimensional comparison processes. We investigated a key assumption of the model that dimensional comparisons mainly depend on the difference in achievement between subjects. We compared correlations between subject‐specific self‐concepts of groups of elementary and secondary school students with or without achievement differences in the respective subjects. Aims: The main goals were (1) to show that effects of dimensional comparisons depend to a large degree on the existence of achievement differences between subjects, (2) to demonstrate the generalizability of findings over different grade levels and self‐concept scales, and (3) to test a rarely used correlation comparison approach (CCA) for the investigation of I/E model assumptions. Samples: We analysed eight German elementary and secondary school student samples (grades 3–8) from three independent studies ( N s 326–878). Method: Correlations between math and German self‐concepts of students with identical grades in the respective subjects were compared with the correlation of self‐concepts of students having different grades using Fisher's Z test for independent samples. Results: In all samples, correlations between math self‐concept and German self‐concept were higher for students having identical grades than for students having different grades. Differences in median correlations had small effect sizes for elementary school students and moderate effect sizes for secondary school students. Conclusions: Findings generalized over grades and indicated a developmental aspect in self‐concept formation. The CCA complements investigations within I/E‐research.